Challenging case of tumour-induced osteomalacia. Issue 5 (19th May 2022) - Kumar, Piyush; Jadhav, Dnyaneshwar V; Ravat, Sangeeta Hasmukh; Jain, Neeraj
Abstract : Tumour-induced osteomalacia (TIO), also known as oncogenic osteomalacia, is an uncommon paraneoplastic syndrome which poses a diagnostic challenge. The hallmark feature is severe acquired hypophosphataemic osteomalacia due to renal phosphate wasting because of increased secretion of fibroblast growth factor 23 (FGF-23). A man in his 30s, presented with a 4-year history of severe muscle aches, bone pain and proximal muscle weakness, was referred for evaluation. His laboratory examination revealed severe hypophosphataemia as a result of urinary phosphate wasting, low 1, 25-dihydroxyvitamin D, high alkaline phosphatase and elevated FGF-23. We could localise the tumour to his right femur and the biopsy showed a mesenchymal origin. The treatment with pharmacotherapy and radiofrequency ablation helped in the normalisation of blood chemistry and resulted in significant clinical improvement. Hypophosphataemia, phosphaturia, elevated FGF-23 and low 1, 25-dihydroxyvitamin D level with severe musculoskeletal pain and muscle weakness necessitate careful evaluation of TIO.